Peranan Produk Pembiayaan Syariah Dalam Mendorong Pertumbuhan UMKM Pada KSPPS SAMARA Sukoharjo - Romadoni, Fitria (Jurnal Ilmiah Ekonomi Islam, 2024)
The growth of Micro, Small and Medium Enterprises (UMKM) is an important focus in supporting a country's economic development. Sharia financing, as a financial instrument based on Islamic principles, offers a significant alternative to support UMKM. This research aims to explore the role of sharia financing products in encouraging UMKM growth, their impact on UMKM growth, as well as supporting and inhibiting factors for the implementation of sharia financing. This research uses a qualitative model with data collection techniques using interview, observation and documentation techniques. The data obtained came from interviews with KSPPS Samara, members and several KSPPS Samara documentation data. The results of the research are: 1) KSPPS plays a positive role in community welfare in various sectors: a) Trade Sector, financing is used for additional business capital and purchasing trade needs. b) Services Sector, used to purchase workshop equipment for motorbike and tire repair services, as well as food and drink services (catering). c) Household sector, used to renovate houses, finance education, purchase motorbikes and meet daily needs. 2) The obstacles faced by KSPPS Samara are: a) Constraints of limited liquidity, the high demand for loans exceeds KSPPS capabilities. b) Constraints in terms of risk level, many UMKM apply for loans and have a high level of risk. c) Lack of collateral or security, which creates doubt in making decisions about granting loans. d) technological and infrastructure limitations. These limitations can slow down the process of applying for financing, evaluating risks and completing transactions.